ANTHROPOLOGICAL LINGUISTICS STUDY ON COMMERCIAL NAMES OF DRUGSTORES IN SURABAYA - Ardhan, Dhea (Universitas Samudra, 2023)
Names became a part of culture because they always occurred in the interaction between people and a language community as well as their environment. As a consequence, naming activity could be considered as a specific linguistic activity that could be intimately linked with values and traditions. The activity of naming was not found in personal and place names only, but was also found in the context of business or commercial activity. One of the phenomena of commercial naming could be found in the drugstore names. This study aimed to investigate the names of drugstore in Surabaya. The theories that were applied in conducting this study were related to anthropological linguistics, onomastics, and company names. The data in this study were the names of drugstores in Surabaya, East Java. The samples were 21 drugstores that were taken in Surabaya. There were five classifications of drugstore naming found, which were associated with personal names, good wishes, pharmaceutical terms, abstract names, and location. By naming the drugstores with certain categories, it definitely had a further commercial purpose. By establishing such trademarks, the naming of the drugstore could be easily remembered by the consumers.